PERANCANGAN PANTI REHABILITASI NARKOBA DI PROVINSI GORONTALO DENGAN PENDEKATAN ARSITEKTUR ORGANIK - Ahmad Djafar (Jurnal Teknik Sipil, Arsitek, Perencanaan Wilayah (J-TSIAP), 2022)
This design aims to make a design for drug rehabilitation parlors in Gorontalo Province. This research is located at the Regional General Hospital (RSUD) Tombulilato Bone Bolango Regency, Gorontalo Province. This study using an organic architectural approach that emphasizes the principles of nature. Through this approach, the comfort of temperature and fresh air are important aspects in choosing an organic architectural approach. This design is by the design standards for rehabilitation buildings, such as safety, comfort, health, and beauty. Based on the design results, the design location is in Huluduatamo Village, Suwawa District, Bone Bolango Regency, Gorontalo Province. The design objects in this study include recreational aspects, educational aspects, therapeutic aspects, and conservation aspects. The determining factors themselves, consisting of achievement and transportation system, physical site conditions, surrounding environmental conditions, facilities and utilities, and site area. Meanwhile, the concept of building design uses a rational method, with a two-story building structure, with a reinforced concrete construction structure system with iron and concrete rods. As well as, the selection of adequate facilities and utilities in the rehabilitation process. The design of this final project "Drug Rehabilitation Center" is based on the needs of the region because of the increasing drug trafficking in each region. So that the goal can be realized to create a design for the Rehabilitation of Drug Victims following its function and characteristics. With the rampant circulation of these goods, there needs to be attention from the provincial government of Gorontalo, namely by building a Rehabilitation Center to socialize the dangers of drugs and cure addicts from dependence on these prohibited items.